Does Service Innovation, Reputation Risk, and Word of Mouth Impact Customer Behavior in Choosing Islamic Banking? An Empirical Evidence in Indonesia - Widayanti, Ipuk (Institut Agama Islam Negeri Ponorogo, 2023)
Indonesia is a country with the largest Muslim population in the world. However, since Islamic banks were established in Indonesia in about 20 years, the participation of Muslims in using Islamic banks is relatively low. The purpose of this study is to analyze and find out the impact of service innovation, reputation risk, and word of mouth on customer behavior in choosing Islamic banks as a place for financing, investing, and so on. The research method uses quantitative. with an experimental and survey approach. Probability sampling of 250 questionnaires distributed to customers throughout Indonesia. The research findings show that service innovation and reputation risk have good external validity to the culture of Indonesian society. The most interesting finding is that the word-of-mouth variable greatly increases customer intention and participation in choosing an Islamic bank. Therefore, this research recommends targeting community leaders or opinion leaders to explain Islamic banking to the whole community.